A study of histological changes of human placenta in rural population of eastern India - Karmakar, Mrinal Kanti; Kar, Sambit; Kumar, S. M.; Chattopadhyay, Subir Kumar; Vaid, L. K.; Sen, Sukanta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Placenta is essential for maintenance of pregnancy and for promoting normal growth and development of fetus. It forms the morphological record of anatomical condition, intrauterine events and intrapartum events of gestation. Present study has been undertaken to record the data on the morphology and histology of placenta from mothers with hypertension and diabetes. Methods: This study showed several significant morphological and histological differences in the placenta of the mother with GDM and hypertensive placenta. The histological study of the placenta was done under microscope and number of syncytial knots, cytotrophoblastic cellular proliferation, fibrinoid necrosis, endothelial proliferation, calcified and hyalinised villous spots were noted per low power field in the diabetics and hypertensive group in comparison to control group. Results: All other parameters including area, thickness, diameter, and circumference of GDM placenta show a significant increase when compared with normal placenta. The gross anatomic features of placentae e.g infarcted areas, calcified areas and marginal insertion of the umbilical cord in the study group show significant increase in value (p>0.01) in diabetic and hypertensive groups when compared to that of the control or normal group. Conclusions: In present study we found that hypertensive placentae tend to be slightly smaller in size, weight, volume, area, thickness, diameter, circumference and feto-placental ratio than normal placentae but the parameters were found to be significantly greater than that of normal placentae in case of diabetic placentae. No significant differences were found in umbilical cord insertion. In normal pregnancy cases we found several histological findings which were increased in hypertensive and diabetic cases.